Use of Over-The-Counter Analgesics Is Associated with Pain, Stress, and Quality of Life in Norwegian Adolescents: A Cross-Sectional Study - Siv Skarstein; Sølvi Helseth; Milada Cvancarova; Kristin Haraldstad; Gudrun Rohde; Hilde Timenes Mikkelsen; Erik Grasaas (MDPI AG, 2024)
Introduction: Approximately 20% of Norwegian adolescents are frequently using Over-the-Counter Analgesics (OTCAs). The WHO emphasizes the need for research to identify the key determinants of health problems in adolescence. Thus, our aim was to describe and explore pain, stress, and Health-Related Quality of Life (HRQOL) in Norwegian adolescents and investigate possible associations upon high/low usage of OTCAs. Methods: This cross-sectional study included 315 adolescents (92 boys, 223 girls) with an average age of 14.1 years (13-15 years). All participants reported using OTCAs. Weekly usage was categorized as high and less than weekly as low. Using a validated questionnaire, we explored the following variables: pain, as measured using the Brief Pain Inventory, stress (Perceived Stress Questionnaire), and HRQOL (KIDSSCREEN-27). Binary logistic regression models were conducted using IBM SPSS Statistics (version 27). Results: Our descriptive findings reveal that high users of OTCAs reported higher pain intensity of 3.4 (SD = 1.9) and perceived stress of 0.38 (SD = 0.18) compared to low users, who reported 2.5 (SD = 1.9) and 0.32 (SD = 0.16), respectively. High OTCA users reported lower average scores than low users across all HRQOL subscales. Binary logistic regression revealed 30% higher odds for higher levels of pain intensity and 14 times higher odds of perceived stress associated with being a high user of OTCAs compared to a low user. Conclusions: Our study shows significantly higher odds for experiencing pain and stress among adolescents using OTCAs daily-to-weekly, compared to those seldom using such medicines. Health professionals should be aware of young people who have a high consumption of OTCAs and investigate whether the use is related to pain or stress. This might be important in designing a personalized and appropriate intervention. Parents and caregivers have an important responsibility in supporting adolescents' appropriate pain management. Longitudinal studies are needed to better explore predictive factors of OTCA use in adolescents, particularly in relation to psychological variables such as stress and quality of life.